Experimental studies on volute-impeller interactions pf centrifugal compressors having vaned diffusers - Georgakis, C. (Cranfield University, 2003)
It is well recognised that the volute plays a important role on the stage performance of a turbo machine in terms of pressure recovery, losses, efficiency and flow range, in addition to influencing stability and radial loads. Although there is a demand for further improvements in efficiency and operating range of compressor components, less attention has been paid to the effect of volute design. The goal of the present study was to experimentally measure the flow through a high pressure ratio 5:1 centrifugal compressor incorporating a vaned diffuser and a volute as part of a fully representative, production version turbocharger test facility. By running the unit as in a gas turbine cycle' (that is with the compressor flow passed through the combustors and then through the hot axial turbine of the turbocharger) it was possible to generate the 1.2MW of power that the test compressor required at its design point. This approach allowed the compressor to be tested at a duty that was relevant to todays industrial needs. The present study shows that the source of the circumferential pressure distortion at the impeller tip was the non-axisymmetric volute. The vaned diffuser did not fully attenuate this distortion, and consequently some of this distortion was measured at the impeller tip. The impeller tip pressure distortion varied as the operating point moved on the compressor characteristic and it was seen to be greatest at the surge point. The performance duties of the compressor components were examined in detail. The radial vaned diffuser had a major influence on both the stage and volute performance, and imposed a very narrow operating range on the test volute. The volute had a nearly constant loss coefficient and the pressure recovery therefore mainly depended on the dynamic head at the volute inlet at the duty points encountered on the tests. The test volute was modified to have a cutback° tongue which gave a better compressor matching at high flows. The flow pattern at the impeller exit was seen to comprise two distinct regions, firstly a wake° or accumulation of low relative energy fluid which occupied most of the shroud surface and extended towards the suction side, and secondly a lower loss flow which was present at the hub pressure comer. The survey also investigated the structure of the flow in the test volute. The volute did not operate as a constant pressure collector° and there was a swirling flow within it. This Vortex distribution was seen to depend on the radial velocity distribution at the volute inlet. Larger radial velocities contributed to stronger swirling flows. The lowest total pressure showed itself in the core of the Vortex over the volute cross sections. There was a radial decrease of the tangential velocities from the inner to the outer radius of the volute cross sections. The flow into the test volute is not uniform. Additional insight into the nature of the compressor flows was derived from a complimentary CFD analysis which is also described.